NGOs using '1Malaysia' must be responsible - Razali - Borneo Post, (KK) (Borneo Post (KK), 2013)
MUAR: All non-governmental organisations(NGOs)using the word '1Malaysia' must be responsible and have the skills and clear facts on any issue, to prevent tarnishing the government's image, said Umno Institute of Higher Education Bureau chairman Datuk Razali Ibrahim.